Neck pain relate with working posture in Dentists - Taweekan Vannajak, Pimonpan; Sae-Lee, Daraporn; Plangkoon Jorns, Teekayu; Boonprakob, Yodchai (Archives of Allied Health Sciences, 2019)
Neck pain is a musculoskeletal disease found in the general populations and may have related to occupations, especially dentists. Neck pain can be caused by an imbalance posture during dental treatment for a long time. An imbalance posture for a long time can induce pain at other regions such as shoulder elbow wrist hand and back. Corrected posture with the concept of ergonomics may decrease loading of muscles and joints. Physical therapy treatment and stretching the muscles are another way to treat neck pain. However, strengthening exercise should be recommended for decreased pain in permanently. Key words: